Pension Plan Funding and Stock Market Efficiency - FRANZONI, FRANCESCO; MARÍN, JOSÉ M. (Journal of Finance, 2006)
ABSTRACT The paper argues that the market significantly overvalues firms with severely underfunded pension plans. These companies earn lower stock returns than firms with healthier pension plans for at least 5 years after the first emergence of the underfunding. The low returns are not explained by risk, price momentum, earnings momentum, or accruals. Further, the evidence suggests that investors do not anticipate the impact of the pension liability on future earnings, and they are surprised when the negative implications of underfunding ultimately materialize. Finally, underfunded firms have poor operating performance, and they earn low returns, although they are value companies.